Health, nutrition and food demand [ - Chern, Wen S.; Rickertsen, Kyrre (Wallingford, UK : CABI, 2003)
This book discusses the likely impacts of health information on the demand for various foods in various countries and among various socioeconomic groups. The effects of types of information such as food scares related to mad cow disease and advertising re also discussed. The book serves as reference for researchers in the food industry and government, as well as a supplementary textbook in courses in applied
1. Introduction -- 2. Health, nutrition and demand for food : an American perspective -- 3. Health, nutrition and demand for food: a European perspective -- 4. Double impact : educational attainment and the macronutrient intake of US adults -- 5. Assesing the importance of health information in relation to dietary intakes in the USA -- 6. A sample selection model with endogenous health knowledge : egg consumption in the USA -- 7. Health information and food demand in Eastern and Western Germany -- 8. Health information and food demand in France -- 9. The impact of nutrient intake on food demand in Spain -- 10. Health information and unstable effects from autocorrelation -- 11. Relative impacts of health information and advertising on commodity markets : US meats -- 12. The impact of dietary cholesterol concerns on consumer demand for eggs in the USA -- 13. Employing an environmental taxation mechanism to reduce fat intake -- 14. How do markets respond to food scares? -- 15. Assessment of findings and future research
Includes bibliographical references and index
Keywords: Food consumption; Food habits; Food supply; Health education; Nutrition; Public health